A legal proposal for the defence of biodiversity: An Environmental Court for Latin America and the Caribbean - Távara Córdova, Francisco (2020)
Latin America and the Caribbean are, indisputably, regions that, due to their privileged geographical location, host a remarkable diversity of flora and fauna species in their territory. For this reason, the protection of this biodiversity is a duty of all Latin American, Caribbean and all humanity, which must be protected through thecourts. To guarantee adequate protection of biodiversity, the study proposes the amendment of article 19.2, literal a, of the Regional Agreement on Access to Information, Public Participation and Access to Justice in Environmental Matters in Latin America and the Caribbean, and the creation of an Environmental Tribunal forLatin America and the Caribbean, which is competent to hear cases of state non-compliance with the environmental protection duties established in the agreement.